Survey on management practices adopted in the transportation of vaquejada horses in the state of Rio Grande do Norte - Silva, Leanderson Paiva da; Oliveira Filho, Paulo Eduardo de; Melo, Ubiratan; Ferreira, Cintia; Faraj, Khaled Salim Dantas Aby (Revista de Ciências Agroveterinárias, 2024)
The care in the transportation of horses has become essential in equine production, particularly stressful for those unfamiliar with it. Faced with a lack of data related to the transportation practices of athletic horses adopted in Brazil, this study aimed to conduct a survey on aspects related to the handling of transportation of rodeo horses in the state of Rio Grande do Norte. The target population for this survey was residents of the state of Rio Grande do Norte associated with the road transportation of horses for sports purposes. After obtaining oral and/or written consent, the authors individually applied the questionnaires to the respondents. Owners answered the questionnaire independently, except when the respondent was illiterate or had some disability, without influencing the responses. Each questionnaire consisted of 45 questions, including 11 open-ended and 34 objective questions. The interviews were conducted at rodeo events in the state of Rio Grande do Norte, and a total of 82 questionnaires were completed. The results highlight the importance of adopting and improving appropriate practices in pre-transport, during transport, and post-transport management.